Single-Cell Transcriptome Profiling Identifies Phagocytosis-Related Dual-Feature Cells in A Model of Acute Otitis Media in Rats - Rao, Yufang; Zhong, Dalin; Qiu, Ke; Cheng, Danni; Li, Li; Zhang, Yi; Mao, Minzi; Pang, Wendu; Li, Daibo; Song, Yao; Li, Junhong; Dong, Yijun; et al. (Frontiers in Immunology, 2021)
Background: The molecular mechanisms of acute otitis media (AOM) development, and the intercellular crosstalk within the multicellular ecosystem of AOM, are not clear. Methods: We established a model of AOM in rats (with normal rats as controls) and undertook single-cell RNA sequencing (scRNA-seq) for the middle-ear mucosa (MEM). Cell clustering and trajectory analyses were undertaken using Seurat and Monocle 3 packages in R software. Pathway analyses were done by gene set enrichment analysis (GSEA). Cell–cell interactions were inferred by CellChat. Cell scores were calculated to identify cells with dual-feature. Results: A total of 7023 cells from three samples of inflamed MEM and 5258 cells from three samples of healthy MEM underwent scRNA-seq, which identified 20 cell clusters belonging to eight major cell types. After exposure to lipopolysaccharide, the MEM underwent significant conversion of cell types characterized by rapid infiltration of macrophages and neutrophils. M2 macrophages seemed to play a key part in inflammatory intercellular crosstalk, which facilitated the maintenance and proliferation of macrophages, cell chemotaxis, and regulation of the proinflammatory activities of cytokines. Three rare cell clusters with phagocytosis-related dual-feature were also identified. They coexisted with professional phagocytes in the MEM, and displayed distinct immunoregulatory functions by maintaining a normal immune microenvironment or influencing inflammation progression. Conclusions: Macrophages might be the “master” initiators and regulators of the inflammatory response of the MEM to external stimuli. And their functions are fulfilled by a specific polarization status (M2) and sophisticated intercellular crosstalk via certain signaling pathways. Besides, the coexistence of professional phagocytes and non-professional phagocytes as well as their interplay in the MEM provides new clues for deciphering the underlying pathogenic mechanisms of AOM.